Energy-saving thermoelectric generator for powering the cooling apparatus of heatgenerating electronic components - Kh. M. Gadzhiev; S. M. Gadzhieva; P. S. Magomedova; A. M. Kurbanov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The article discusses energy-saving thermoelectric generators for autonomous power supply of the cooling apparatus of heat-generating electronic components.Method. Methods of modeling heat exchange processes in the operation of thermoelectric generators based on the Seebeck effect are applied. The heated and cooled zones of the generator are topologically spaced to reduce parasitic conductive transport. The semiconductor branches are manufactured using thin-film technology to reduce parasitic Joule heat emissions. The materials of the junctions and electrodes are selected taking into account the energy of the electrons.Result. Energy saving of processes has increased in thermoelectric generators by reducing parasitic Joule heat generation, reducing parasitic conductive transfer and additional energy generation from metal electrodes.Conclusion. The conducted studies allow us to conclude that in order to increase the energy saving of thermoelectric generators for autonomous power supply of the cooling apparatus of the heat-generating electronic components, it is necessary to topologically separate the heated and cooled zones of the generator into different levels in space, and to manufacture semiconductor branches using thin-film technology and additionally cool the generator junctions with ventilation, and additionally recover energy from the heat-generating components on the heated junctions.